A study on evaluation of solitary nodular thyroid lesions by FNAC and its histopathological correlation - Karim, Md Iqbal; Nachev, Rosen; Fuklev, Nikolay; Nargis, Nazlima (Bangladesh Journal of Medical Science, 2019)
Background: Solitary nodular enlargement of thyroid is one of the common indications for surgical excision. Since most of the nodules are benign, symptomless, normal thyroid hormone profile, they do not require excision. This study was done to evaluate the utility of FNAC as a rapid diagnostic method in various thyroid lesions and guide the clinician for further treatment. Objective: This main objective of the study to evaluate the cyto-histopathological findings, and the accuracy of fine needle aspiration cytology (FNAC) procedure in solitary nodular thyroid lesions. Materials and Methods: This prospective study comprises total 160 cases with thyroid lesions referred to cytopathology laboratory and gland morphology studied by ultrasonography (USG). Based on ultrasonography report Fine Needle Aspiration were done manually or guided and aspirated material fixed on fixative and stained to examine. Results: Age incidence varied from 10-80 yrs. The commonest age group affected was 21-40 yrs. The ratio of male to female was 1:2.2. The duration of symptoms ranged from 10 days to 15 years. Maximum number of cases presented with midline swelling of the neck. On cytology 52 (32.5%) cases were diagnosed as colloid goiter, 46 (28.75%) as colloid goiter with cystic change, 16(10%) as thyroiditis - among them 6(3.75%) as granulomatous thyroiditis, 8(5%) as lymphocytic thyroiditis, 2(1.25%) as dequervain thyroiditis, 10 (6.25%) as follicular neoplasm, 2(1.25%) as hurthle cell adenoma, 5(3.3%) as papillary carcinoma, 2 (1.25%) as medullary carcinoma, 1(0.33%) anaplastic carcinoma and 1(0.33%) NHL as suspicious smear. Histopathological examination was possible in 60 cases. The overall sensitivity was 90.2%, specificity was 98.2% and accuracy was 97.1%. Conclusion: FNAC is a rapid, efficient, cost-effective, relatively painless procedure and produces a early result with a high diagnostic accuracy. It has high rates of sensitivity and specificity to diagnose the solitary thyroid lesions and thereby it is an important diagnostic tool and further management of patients with thyroid lesions. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.789-795